2018
DOI: 10.1016/j.jpeds.2018.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of Treating Neonatal Hypoglycemia with Dextrose Gel

Abstract: Australian New Zealand Clinical Trials Registry: ACTRN12608000623392.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 15 publications
1
13
0
2
Order By: Relevance
“…Although in our study we did not directly perform a cost analysis, we observed the results of similar studies in literature [23] and we can assume that a reduced number of NICU admission, less iv treatment and a shorter length of hospitalization, make dextrose oral gel a less costly option for the management of neonatal asymptomatic hypoglycemia.…”
Section: Discussionsupporting
confidence: 50%
“…Although in our study we did not directly perform a cost analysis, we observed the results of similar studies in literature [23] and we can assume that a reduced number of NICU admission, less iv treatment and a shorter length of hospitalization, make dextrose oral gel a less costly option for the management of neonatal asymptomatic hypoglycemia.…”
Section: Discussionsupporting
confidence: 50%
“…A 2-year follow-up established safety by demonstrating similar rates of processing difficulty and neurosensory impairment between the oral dextrose and placebo groups ( 48 ). A subsequent cost-utility analysis concluded that dextrose gel resulted in a cost-saving of US$782 per baby ( 49 ).…”
Section: Management Of Neonatal Hypoglycemiamentioning
confidence: 99%
“…The overall lifetime cost was considered to be the sum of the initial postnatal hospital costs, and the cumulative annual total post-discharge healthcare expenditure specifically for each outcome over the time horizons of the analysis, discounted at 3.5% [ 44 , 45 ] for costs incurred in timeframes greater than 1 year. Postnatal hospital costs were based on the lengths-of-stay in a general postnatal ward and a neonatal intensive care unit (NICU), and their costs, as described previously [ 6 ], and were converted and inflated to 2018 NZ$ using the methods outlined above. The average cost of a postnatal hospital stay used for an infant with neonatal hypoglycaemia was NZ$7500, and for an infant without neonatal hypoglycaemia was NZ$1100.…”
Section: Methodsmentioning
confidence: 99%
“…Short-term costs have been described previously for infants at increased risk of neonatal hypoglycaemia [ 6 ], but there remains a paucity of high quality prospective evidence examining the post-discharge outcomes of neonatal hypoglycaemia [ 5 , 7 ], and their costs. We have undertaken an economic analysis to compare the costs and utilities for subjects who experienced neonatal hypoglycaemia and those who did not, with the objective of quantifying the total cost burden due to neonatal hypoglycaemia, and, via net monetary benefit loss estimations, an indication of the impact of longer term outcomes useful for future economic evaluations of preventative treatments.…”
Section: Introductionmentioning
confidence: 99%